The time‐resolved atomic, molecular and optical science instrument at the Linac Coherent Light Source. (19th May 2022) - Walter, Peter; Osipov, Timur; Lin, Ming-Fu; Cryan, James; Driver, Taran; Kamalov, Andrei; Marinelli, Agostino; Robinson, Joe; Seaberg, Matthew H.; Wolf, Thomas J. A.; Aldrich, Jeff; Brown, Nolan; et al.
Abstract : The newly constructed time‐resolved atomic, molecular and optical science instrument (TMO), configured to take full advantage of both linear accelerators at SLAC National Accelerator Laboratory, the copper accelerator operating at a repetition rate of 120 Hz providing high per‐pulse energy as well as the superconducting accelerator operating at a repetition rate of about 1 MHz providing high average intensity, is described. Abstract : The newly constructed time‐resolved atomic, molecular and optical science instrument (TMO) is configured to take full advantage of both linear accelerators at SLAC National Accelerator Laboratory, the copper accelerator operating at a repetition rate of 120 Hz providing high per‐pulse energy as well as the superconducting accelerator operating at a repetition rate of about 1 MHz providing high average intensity. Both accelerators power a soft X‐ray free‐electron laser with the new variable‐gap undulator section. With this flexible light source, TMO supports many experimental techniques not previously available at LCLS and will have two X‐ray beam focus spots in line. Thereby, TMO supports atomic, molecular and optical, strong‐field and nonlinear science and will also host a designated new dynamic reaction microscope with a sub‐micrometer X‐ray focus spot. The flexible instrument design is optimized for studying ultrafast electronic and molecular phenomena and can take full advantage of the sub‐femtosecond soft X‐ray pulse generation program.